Feasibility of ECC with high contents of post-processed bagasse ash as partial cement replacement. (14th February 2022) - Subedi, Sujata; Arce, Gabriel A.; Hassan, Marwa M.; Barbato, Michele; Mohammad, Louay N.; Rupnow, Tyson
Highlights: Post-processed sugarcane bagasse ash (PBA) is studied as cement replacement in ECCs. Workability of the mixtures decreases for increasing PBA. Use of PBA reduces 28-day compressive strength but increases surface resistivity. PBA outperformed class F fly ash for compressive strength and surface resistivity. PBA increases tensile ductility, but not enough to produce ECCs. Abstract: This study investigated the feasibility of using high contents of post-processed sugarcane bagasse ash (PBA) as a partial replacement of cement for the development of Engineered cementitious composites (ECCs) with low amounts (1.5% by volume) of non-oil-coated polyvinyl alcohol (PVA) fibers. PBA was prepared by sieving, burning, and grinding raw sugarcane bagasse ash collected from a sugar mill. Composites using three different replacement levels of cement with PBA (i.e., 40%, 50%, and 60% by mass) were evaluated and compared to a composite without PBA (i.e., PBA-0) and a composite using Class F fly ash (FA) at 60% cement replacement (i.e., FA-60). This study evaluated fiber-bridging properties via single crack tensile tests (SCTT), matrix properties via fracture toughness tests, mechanical properties via compressive strength and uniaxial tensile tests, and physical properties via surface resistivity and flow tests. Results showed that the workability of the mixtures decreased with the increase in PBA content. Furthermore, the incorporation of PBA resulted in a reduction in compressive strength (up to 39.1%) and improvements in surface resistivity. Importantly, PBA composites outperformed the FA composite in compressive strength and surface resistivity. The use of PBA produced reduction in the crack-tip fracture toughness ( J tip ). SCTT revealed that the complementary energy of the fiber-bridging relation ( J b ' ) was positively affected by PBA up to 50% cement replacement; yet, at 60% cement replacement, J b ' substantially decreased compared to PBA-0. J b ' increments were attributed to a likely decrease in the fiber/matrix interface chemical bond, whereas the decrease at the 60% cement replacement was attributed to fiber clumping due to the poor workability of the mixture. The fiber-bridging capacity and tensile strength of the composites exhibited a similar trend, where the mixture using 40% cement replacement with PBA showed the highest values and the one using 60% showed the lowest value. All PBA-composites exhibited higher tensile strain capacity compared to PBA-0, and the highest improvement (i.e., 82.1%) was observed at 50% cement replacement with PBA. However, the tensile ductility of the PBA composites was significantly lower than that of FA-60. It is concluded that PBA can generate comparable fiber-bridging properties as those produced by FA; however, FA is more effective at reducing J tip, thus producing better conditions for pseudo-strain hardening behavior. Furthermore, the use of high contents of PBA significantly reduces the workability of the composites inhibiting proper fiber dispersion. Therefore, large amounts of PBA as partial cement replacement cannot be used to produce ECCs in conjunction with low amounts of non-oil-coated PVA fibers.